An Assistive Bag for Blind and Deaf - Joselin Retna Kumar, G; ., Showme; Saxena, Purva; Kumar Mamidala, Uday; Pammi, Anupam (International Journal of Engineering and Technology, 2018)
People with disabilities who use visual aids like hearing aid, blind stick for obstacle detection while walking etc. are often discriminated in the society as they are handicapped. The main focus of this paper is to create an assistive device for the visually impaired as well as the deaf to make them socially acceptable without showing their disability to the society by using visible aid. It is incorporated with features like GPS location update, GSM-based messaging system to notify relatives of the location of the user in case of emergency situations and voice recognition based home automation. It uses ultrasonic sensors to detect obstacles and vibration motors to notify the user about the obstacle thus eliminating the use of external device for communication.Â Â